Polyphyletic origin of Brassica juncea with B. rapa and B. nigra (Brassicaceae) participating as cytoplasm donor parents in independent hybridization events1. Issue 7 (1st July 2014) - Kaur, Puneet; Banga, Shashi; Kumar, Nitin; Gupta, Shilpa; Akhatar, Javed; Banga, Surinder S.
Abstract : Premise of the study: Brassica juncea is a major source of edible oil in the Indian subcontinent and northern China. It is also used as a root and leaf vegetable in China and as a condiment in Europe and America. There is a long‐standing view that B. juncea originated from multiple hybridization events between B. rapa and B. nigra and that hybridizations were always unidirectional with B. rapa as the cytoplasmic donor. These conclusions were, however, centered primarily on nuclear markers. Methods: Two hundred forty‐six accessions of B. juncea, B. rapa, and B. nigra were genotyped using chloroplast and nuclear simple sequence repeat (SSR) markers. Key results: Astructure analysis assigned B. juncea germplasm (122) into three major groups based on plasmotype variation. The bulk of Indian B. juncea genotypes were grouped along with Chinese and Australian accessions. This plasmotype was absent in sampled accessions of B. rapa (97), B. nigra (27), and other wild crucifers (10). The second group of B. juncea included East European genotypes and four accessions from India. It showed unambiguous homology with the predominant B. nigra plasmotype. The neighbor joining tree produced seven subgroups, arranged into two broad lineages. The first lineage included Indian, Australian, and Chinese B. juncea genotypes; it was associated with wild species belonging to the " rapa " lineage. Nuclear SSR marker‐based analyses were largely supportive of results from chloroplast SSR analyses. Conclusions: Based on these results, we provide the first report that B. juncea originated several times with both B. rapa and B. nigra as cytoplasmic donors in separate hybridization events.